2020
DOI: 10.12688/f1000research.20510.1
|View full text |Cite
|
Sign up to set email alerts
|

All disease begins in the (leaky) gut: role of zonulin-mediated gut permeability in the pathogenesis of some chronic inflammatory diseases

Abstract: Improved hygiene leading to reduced exposure to microorganisms has been implicated as one possible cause for the recent “epidemic” of chronic inflammatory diseases (CIDs) in industrialized countries. That is the essence of the hygiene hypothesis that argues that rising incidence of CIDs may be, at least in part, the result of lifestyle and environmental changes that have made us too “clean” for our own good, so causing changes in our microbiota. Apart from genetic makeup and exposure to environmental triggers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
181
1
27

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(251 citation statements)
references
References 108 publications
(14 reference statements)
7
181
1
27
Order By: Relevance
“…However, based on our results, we assume that after birth inflammatory processes in the gut tend to decrease over time save the increased permeability of antigens shaping immune tolerance. However, this mechanism may also contribute to the pathogenesis of chronic inflammatory diseases in genetically susceptible individuals [72].…”
Section: Discussionmentioning
confidence: 99%
“…However, based on our results, we assume that after birth inflammatory processes in the gut tend to decrease over time save the increased permeability of antigens shaping immune tolerance. However, this mechanism may also contribute to the pathogenesis of chronic inflammatory diseases in genetically susceptible individuals [72].…”
Section: Discussionmentioning
confidence: 99%
“…Zonulin is a modulator intercellular tight junction involved in the regulation of intestinal permeability. It has been shown that serum zonulin levels are increased in patients with IBD compared to healthy controls [8] (while no studies are present in the literature comparing levels in patients with IBD and levels in patients with gastrointestinal symptoms without clear inflammation, like patients affected by irritable bowel symptoms (IBS)) and are associated with higher levels of pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNFα) and interleukin (IL)-6 [9], which play a key role in promoting mucosal inflammation [10]. Activated macrophages contribute to the immunological response as well.…”
Section: Introductionmentioning
confidence: 99%
“…Препаратом выбора является парацетамол в дозе 1000 мг не более 4-х раз/сут. [12,13]. Важным компонентом лечения является выполнение дыхательных упражнений и отдых в положении на животе.…”
Section: хронический коронарный синдромunclassified